ChemInform Abstract: [3, 3]‐Sigmatropic Rearrangement/Allylboration/Cyclization Sequence: Enantioenriched Seven‐Membered‐Ring Carbamates and Ring Contraction to Pyrrolidines. Issue 21 (6th May 2016) - Mace, Aurelie; Touchet, Sabrina; Andres, Patricia; Cossio, Fernando; Dorcet, Vincent; Carreaux, Francois; Carboni, Bertrand
Abstract: The title reaction sequence starting from carbamates (I) leads to 6, 7‐dihydro‐1, 3‐oxazepinones (III), which are converted into 1, 3‐oxazepanone (IV), aldehyde (V), and diacetates (VII).